2015
DOI: 10.1002/nur.21663
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of medication nonadherence differ among black and white patients with heart failure

Abstract: Heart failure (HF) is a global public health problem, and outcomes remain poor, especially among ethnic minority populations. Medication adherence can improve heart failure outcomes but is notoriously low. The purpose of this secondary analysis of data from a prospective cohort comparison study of adults with heart failure was to explore differences in predictors of medication nonadherence by racial group (Black vs. White) in 212 adults with heart failure. Adaptive modeling analytic methods were used to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…In this present study, nearly 60% of participants with poor adherence were rehospitalized within 6-months of enrollment. Our findings are in consonance with several other prospective studies which have produced rehospitalization rates ranging between 20 and 69% [16,32,33,38,39]. Additionally, intervention studies have uniformly shown that improved adherence is associated with reduction (3-96%) in readmission risk [40,41,43,44,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this present study, nearly 60% of participants with poor adherence were rehospitalized within 6-months of enrollment. Our findings are in consonance with several other prospective studies which have produced rehospitalization rates ranging between 20 and 69% [16,32,33,38,39]. Additionally, intervention studies have uniformly shown that improved adherence is associated with reduction (3-96%) in readmission risk [40,41,43,44,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 91%
“…With regards to reasons for poor adherence, numerous factors have predominated in various studies. [29,32]. In this present study, nearly 90% of nonadherent participants reported medication cost as the major barrier to their adherence.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Submitted for publication, 2015). Another study reported that African-American heart failure patients had more and different risk factors (more comorbidity, lower serum sodium, higher systolic blood pressure and fewer methods of compensating for forgetfulness) for medication adherence than Caucasians 1. More studies exploring how race and ethnicity influence behaviour are greatly needed.…”
Section: Commentarymentioning
confidence: 99%